Dose‐dependent alkaloid sequestration and N‐methylation of decahydroquinoline in poison frogs. Issue 5 (24th February 2022) - Jeckel, Adriana M.; Bolton, Sarah K.; Waters, Katherine R.; Antoniazzi, Marta M.; Jared, Carlos; Matsumura, Kunihiro; Nishikawa, Keisuke; Morimoto, Yoshiki; Grant, Taran; Saporito, Ralph A.
Abstract: Sequestration of chemical defenses from dietary sources is dependent on the availability of compounds in the environment and the mechanism of sequestration. Previous experiments have shown that sequestration efficiency varies among alkaloids in poison frogs, but little is known about the underlying mechanism. The aim of this study was to quantify the extent to which alkaloid sequestration and modification are dependent on alkaloid availability and/or sequestration mechanism. To do this, we administered different doses of histrionicotoxin (HTX) 235A and decahydroquinoline (DHQ) to captive‐bred Adelphobates galactonotus and measured alkaloid quantity in muscle, kidney, liver, and feces. HTX 235A and DHQ were detected in all organs, whereas only DHQ was present in trace amounts in feces. For both liver and skin, the quantity of alkaloid accumulated increased at higher doses for both alkaloids. Accumulation efficiency in the skin increased at higher doses for HTX 235A but remained constant for DHQ. In contrast, the efficiency of HTX 235A accumulation in the liver was inversely related to dose and a similar, albeit statistically nonsignificant, pattern was observed for DHQ. We identified and quantified the N ‐methylation of DHQ in A. galactonotus, which represents a previously unknown example of alkaloid modification in poison frogs. Our study suggests that variation in alkaloid composition among individuals and species can result from differences in sequestration efficiency related to the type and amount of alkaloids available in the environment. Abstract : Dietary alkaloid sequestration by poison frogs is greater at higher doses, with alkaloids differing in uptake efficiency. N ‐methylation of decahydroquinoline, a previously unknown modification in poison frogs, occurs in Adelphobates galactonotus . Research Highlights: Dietary alkaloid sequestration by poison frogs is greater at higher doses, with alkaloids differing in uptake efficiency. N ‐methylation of decahydroquinoline, a previously unknown modification in poison frogs, occurs in Adelphobates galactonotus .